Evaluasi Kebijakan Akuntansi Biaya Pinjaman Atas Aset Tetap di Indonesia - I Kadek Arik Juana Putra; Amrie Firmansyah (Juara: Jurnal Riset Akuntansi, 2021)
This study aims to determine the implementation of loan cost accounting policies on fixed assets in food and beverage sub-sector companies in Indonesia. Based on purposive sampling, a sample of 18 companies was obtained. The research data is sourced from the financial statements of food and beverage sub-sector companies listed on the IDX from 2012 to 2019 which were obtained from www.idx.co.id and https://www.idnfinancials.com. This study employs a qualitative method with a content analysis approach and interviews. The content analysis method is used to obtain information on the application of borrowing cost accounting policies on property, plant and equipment and information regarding the disclosure of the amount of capitalized borrowing costs and capitalization rates. In addition, the interview method was carried out as a follow-up to obtain the views of experts to elaborate the results of the content analysis on the disclosure of fixed asset loan cost accounting policies. This study concludes that there are 15 out of 18 companies that do not meet the requirements for disclosure of borrowing costs on fixed assets as regulated in PSAK 26.